Pengaruh curah hujan, kelembaban, dan temperatur terhadap prevalensi Malaria di Kabupaten Tanah Bumbu Kalimantan Selatan - Sri Sulasmi; Dian Eka Setyaningtyas; Akhmad Rosanji; Nita Rahayu (JHECDs: Journal of Health Epidemiology and Communicable Diseases, 2017)
Malaria is one of contagious disease which is still a crucial matter in Indonesia. Malaria disease control is being done by decreasing the number of malaria case gradually. South Kalimantan is one of high malaria prevalence province. Malaria cases occur nearly every month with significant raise of malaria occurence on May, October to July. This research intend to know the effect of rainfall, temperature and humidity on to occurence of Malaria case. This is a descriptive research, using secondary data of rainfall, temperature and humidity from Meteorology and Geophysics Board of Banjarbaru and Malaria case of Tanah Bumbu District data within 10 years term. This research shows that rainfall does effect the occurence of Malaria. Temperatur and humidity does effect the occurence of Malaria. This result showed that rainfall does effect raise of mosquito density. Temperature does effect on mosquito density at 26,5 – 27 degree celcius. Humidity does effect on mosquito density at 85-87 percent. This research concludes that climate variable change does not directly effect raise of case.